Nanoparticles as catalysts of agricultural revolution: enhancing crop tolerance to abiotic stress: a review - Cao, Yahan; Turk, Khalid; Bibi, Nabila; Ghafoor, Abdul; Ahmed, Nazeer; Azmat, Muhammad; Ahmed, Roshaan; Ghani, Muhammad Imran; Ahanger, Muhammad Abass (Frontiers in Plant Science, 2025)
Ensuring global food security and achieving sustainable agricultural productivity remains one of the foremost challenges of the contemporary era. The increasing impacts of climate change and environmental stressors like drought, salinity, and heavy metal (HM) toxicity threaten crop productivity worldwide. Addressing these challenges demands the development of innovative technologies that can increase food production, reduce environmental impacts, and bolster the resilience of agroecosystems against climate variation. Nanotechnology, particularly the application of nanoparticles (NPs), represents an innovative approach to strengthen crop resilience and enhance the sustainability of agriculture. NPs have special physicochemical properties, including a high surface-area-to-volume ratio and the ability to penetrate plant tissues, which enhances nutrient uptake, stress resistance, and photosynthetic efficiency. This review paper explores how abiotic stressors impact crops and the role of NPs in bolstering crop resistance to these challenges. The main emphasis is on the potential of NPs potential to boost plant stress tolerance by triggering the plant defense mechanisms, improving growth under stress, and increasing agricultural yield. NPs have demonstrated potential in addressing key agricultural challenges, such as nutrient leaching, declining soil fertility, and reduced crop yield due to poor water management. However, applying NPs must consider regulatory and environmental concerns, including soil accumulation, toxicity to non-target organisms, and consumer perceptions of NP-enhanced products. To mitigate land and water impacts, NPs should be integrated with precision agriculture technologies, allowing targeted application of nano-fertilizers and nano-pesticides. Although further research is necessary to assess their advantages and address concerns, NPs present a promising and cost-effective approach for enhancing food security in the future.